2022
DOI: 10.3390/jcm11237172
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Drug Interactions among Patients Hospitalized with COVID-19 in Greece

Abstract: The modulation of the pharmacological action of drugs due to drug-drug interactions (DDIs) is a critical issue in healthcare. The aim of this study was to evaluate the prevalence and the clinical significance of potential DDIs in patients admitted to the University Hospital of Heraklion in Greece with coronavirus disease 2019 (COVID-19). Cardiovascular disorders (58.4%) and diabetes (types I and II) (29.6%) were the most common comorbidities. A high occurrence of DDIs was observed, and clinically significant D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Herein, we retrospectively studied a cohort of patients admitted to the COVID-19 department of the University Hospital of Heraklion who had been previously treated with a B-cell-depleting monoclonal antibody and identified a mortality of about 15.4% which is a rate similar to that for the general population hospitalized for COVID-19 [ 43 , 44 , 45 , 46 ]. Notably, the mortality noted in patients with previous use of B-cell-depleting monoclonal antibodies was also similar to the mortality in the general population noted in another recent study involving patients hospitalized in the same department as in the present study [ 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Herein, we retrospectively studied a cohort of patients admitted to the COVID-19 department of the University Hospital of Heraklion who had been previously treated with a B-cell-depleting monoclonal antibody and identified a mortality of about 15.4% which is a rate similar to that for the general population hospitalized for COVID-19 [ 43 , 44 , 45 , 46 ]. Notably, the mortality noted in patients with previous use of B-cell-depleting monoclonal antibodies was also similar to the mortality in the general population noted in another recent study involving patients hospitalized in the same department as in the present study [ 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…The highest median DDI index in our study was observed in patients with COVID-19. Notably, in the study by Spanakis and others [28], clinically significant DDIs of "serious-use alternative" or "use with caution-monitor" management were found in 40.3% of cases upon admission, 21% during hospitalization, and 40.7% upon discharge, suggesting that the efforts of a medical team can successfully reduce the risks associated with dangerous DDIs during a hospital stay. It is clear that serious DDIs can hinder treatment response and complicate hospitalization in COVID-19 patients [28].…”
Section: Discussionmentioning
confidence: 95%
“…( Figure 1 ). Contemplating the accumulated evidence derived from experts’ opinions, in silico, in vitro and in vivo data, clinical studies, systematic reviews and meta-analyses, and reports from regulatory authorities that update the Summary of Product Characteristics, potential DDIs can be categorized considering clinical significance as “Serious-Use alternative” (SUA), “Use with caution-Monitor” (Monitor), and “Moderate-Minor” (MM) DDIs [ 4 , 25 , 26 , 27 ].…”
Section: Pharmacological Mechanisms Of Drug Interactionsmentioning
confidence: 99%